Bioinformatics tools for conformational b-cell and t-cell epitope prediction: potential vaccine candidate - VIKAS KAUSHIK,; JOGINDER SINGH, (International Journal of Pharma and Bio Sciences, 2017)
Exploration of sequencing technologies has led to a new concept in vaccination in which isolated epitopes, capable of stimulating a specific immune response, have been identified and used to achieve advanced vaccine formulations; replacing those constituted by whole pathogen-formulations. In this context, bioinformatics approaches play a critical role on analyzing multiple genomes to select the protective epitopes. Identification of epitopes which induce humoral as well as cell mediating responses is an essential issue in the field of immunology. This review presents a comprehensive compilation of the most advantageous online immunological tools to facilitate the design and development of vaccine candidates. To stimulate the development of better servers and to find out potential immune stimulators, some promising directions are also extensively discussed. Vaccination against HCV is challenging being its hypervariable nature. The recent advancement of bioinformatics resources and tools in conformational B-cell and T-cell epitope prediction can be ultimate option for its cure. In this study, we make a systematic review about the bioinformatics resources and tools for conformational B-cell and T-cell epitope prediction.